Sistem Pendukung Keputusan Penentuan Keluarga Miskin Menggunakan Metode Fuzzy Tsukamoto - Sofiansyah Fadli; Maulana Ashari; Saikin Saikin (Journal of Information System Research (JOSH), 2022)
The government, in this case the ministry of national development planning the Republic of Indonesia/national development planning agency has tried to reduce poverty in each region. With articulated the various poverty alleviation programmes, including the presence of cluster I, cluster II, cluster III and cluster IV. Social assistance programs launched by the Government, in particular the first Cluster program got more attention from the citizens of society. There are 14 poverty criteria, which became the reference of criteria for Badan Pusat Statistik (BPS) in determining the poor families that eligible to receive aid from the Government. Poor and not poor membership has a value of 0 and 1, were in fact, poverty has different levels. Determination of the poverty program at this time there is a problem in terms of decision-taking which there are to many subjectivity, for example which is not poor is said to be poor in the data recording/logging. In this paper, a computerized system for determining of a poor family. The method used in this studyis developed Fuzzy Tsukamoto. Tsukamoto Fuzzy method used in the process of selection by holding against 14 criteria. Output of the system can facilitate the Management of the village in taking decisions to determine the recipients of the aid programs initiated by the Governmen. The results based on the accuracy test that has been carried out using a data sample of 7 RUTA, the results obtained are 0.568 (very poor), 0.684 (poor), 0.506 (very poor), 0.697 (poor), 0.577 (very poor), 0.609 (poor). ), and 0.625 (poor). The poverty rate (Fuzzy Results) with Recommendations (Expert Validation) show the same results or results so that the Fuzzy Tsukamoto method can be applied well in poor families in Darmaji Village.